N. F. S. Grundtvigs Dag- og Udtogsbøger I-II, udgivet af Gustav Albeck - Thodberg, Christian (Grundtvig-studier, 1980)
N.F.S. Grundtvig’s diaries and summary books I - II Edited by Gustav Albeck Reviewed by Christian Thodberg The most important Grundtvig publication in 1979 was Professor Gustav Albeck’s edition of Grundtvig’s diaries and summary books. The edition consists partly of texts, partly of detailed comments on names, quotations and contemporary historical events. Grundtvig never wrote a diary as such. His diaries are a mixture of personal impressions and the books he was reading. The diary of 1802-3 is only partly preserved. In 1804 Grundtvig rewrote his 1802-diary with a view to publication. This is one of the earliest examples of his many retrospective surveys of his life, seen from the particular stage he had reached.These retrospective surveys have often paralysed Grundtvig-research, so that it was hard to see what was actually happening. Professor Albeck’s commentaries now prevent any such misunderstandings. The diaries give a first-hand impression of Grundtvig’s literary reading and his interest in linguistic and educational matters. The edition covers the scattered entries from in particular the first decade of the 19th century. For the rest of Grundtvig’s life the personal records are few and far between.Professor Albeck’s exemplary presentation of the material is an invaluable introduction to the authorship of the young Grundtvig. The meticulous commentaries will benefit not least non-Danish readers, since all the necessary contemporary historical information is provided.